Partial characterization of water-soluble mucilage from alugbati (Basella rubra) - Erasquin, Uriel Joseph (2002)
BSTRACT The study was conducted to characterize the water-soluble mucilage present in alugbati leaves. This task was divided into three phases to facilitate it effectively. Phase I involved the collection, verification and drying of the leaves. The next phase dealt with the mucilage extraction process. Lastly, Phase III concerned the characterization process. The purified mucilage was light brown in color with a Munsell color notation of 5Y 8/2. It was found to contain 3.47% phenolic substance, approximately 21.98% available carbohydrate, 55.01% dietary fiber and 15.83% crude protein. The mucilage was acidic in nature and formed the most viscous solution at pH 3. It formed fibrous and sheet-like structures when subjected to freeze-drying. Its infrared spectrum was sufficiently correlated with the components of the mucilage as determined by proximate analysis.